Financial Performance Analysis of Transportation and Logistics Sector Companies Listed On the Indonesia Stock Exchange Using a Financial Ratio Approach in 2014-2024 - Revita Pintania; Mukhzarudfa Mukhzarudfa; Fredy Olimsar (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to analyze the financial performance of transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) during the 2014–2024 period using a financial ratio approach. This study employed a quantitative method with a purposive sampling technique, resulting in 10 companies meeting the research criteria with a total of 110 observations. Financial performance analysis was conducted through three ratio groups: liquidity ratios (current ratio and cash ratio), solvency ratios (debt to asset ratio and debt to equity ratio), and profitability ratios (return on investment and return on equity). The results showed that the financial performance of transportation and logistics companies experienced significant fluctuations during the observation period, particularly during the COVID-19 pandemic and the economic recovery phase. In general, several companies demonstrated good ability to maintain liquidity levels and control their capital structure, despite pressure on profitability in the 2020–2021 period. Based on the comprehensive analysis, PT Eka Sari Lorena Transport Tbk (NELY) and PT Samudera Indonesia Tbk (SMDR) demonstrated relatively better and more stable financial performance compared to other companies during the study period. These findings imply that liquidity management, debt structure, and operational efficiency are important factors in maintaining financial performance stability, particularly in sectors that are sensitive to macroeconomic dynamics.